PERAWATAN PADA PASIEN ANKYLOGLOSSIA - Henry Mandalas; Widya . (Odonto : Dental Journal, 2017)
Background: Ankyloglossia (tongue tie) is a congenital aberration characterized by a thick, toned, or short frenulum that causes limited tongue movement. Lingual frenectomy is performed for the treatment of patients with ankyloglossia. After surgery the patient can lift the tongue to the palate and can reach the labial portion of the maxillary left and right teeth. The purpose of this case report is to report frenectomy treatment in the lingual frenulum. Case Management: The 14-year-old female patient felt the tongue could not be lifted to the palate and it was difficult to clean the labial portion of the maxillary left and right teeth. On clinical examination the patient’s lingualis frenulum is short. The patient get prophylaxis treatment followed by a lingualis frenectomy surgery. Result: After 1 month control, the patient can lift the tongue to the palate and can clean the labial portion of the maxillary right and left teeth